THE INTERPLAY BETWEEN PSYCHOLOGICAL CONTRACTUAL BREACH, SUPERVISOR TRUST, AND ORGANIZATIONAL INJUSTICE IN CONSTRUCTION INDUSTRY - Marwat, Athar; Adnan, Dr. Adil; Ali, Dr. Amna (Journal of Business & Tourism, 2022)
This study evidences the psychological contract breach and organizational injustice affect via negative influence of employees’ supervisor trust. Questionnaire survey was sent to the individual at the construction site for data collection. The sample comprises 194 full-time employees. After initial data normality & reliability testing, we conducted confirmatory factor analysis to assess validity of measures with AMOS. The results of our empirical study show that when faced with psychological contracts breaches, and injustice in the workplace, employees are less likely to trust supervisor and most likely to engage in neglecting behaviors. In view of these results, it was suggested that construction supervisors plan policies and strategies to facilitate implementation of an appropriate environment. It will also provide positive culture; where-ever employees more frequently execute behavior in the low breach of psychological contract with the justice environment.